Nutrient requirement and distribution of intensively grown ‘Brookfield Gala’ apple trees - Kangueehi, Grace Nandesora (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MscAgric (Horticulture))--University of Stellenbosch, 2008.